High wintertime particulate matter pollution over an offshore island (Kinmen) off southeastern China: an overview - Hsu, S. C.; Liu, S. C.; Tsai, F.; Engling, G.; Lin, I. I.; Chou, C. K. C.; Kao, S. J.; Lung, S. C. C.; Chan, C. Y.; Lin, S. C.; Huang, J. C.; Chi, K. H.; et al. (American Geophysical Union, 2010)
Both the Yangtze River Delta (YRD) and the Pearl River Delta (PRD), the two most rapidly developing areas in eastern China, have suffered from serious air pollution, and thus, numerous investigations were devoted to studying these problems. Other areas in eastern China have received less attention despite similar rapid development in their industries and economy. In this study, we analyzed air‐quality data from Kinmen Island (24°27′26′′N, 118°19′36′′E) located off Fujian Province and between the two above‐mentioned deltas. Our results clearly show that the study area is experiencing serious air quality deterioration. Particularly, high levels of suspended particulate matter (PM) were observed during winter, when the northeasterly monsoon prevails. For example, concentrations of wintertime PM10 (particles ≤ 10 mm in diameter) frequently exceeded 100 mg/m3 in the last three years. In addition to the air‐quality data analysis, aerosol samples were collected between 22 November 2007 and 6 March 2008 and subjected to chemical analyses of various species. Our findings show that the three principal PM components include organic, mineral, and sulfate species with moderate to minor fractions of nitrate, sea salt, elemental carbon, and trace metal oxides. The high PM levels observed over the island may be partly attributed to the transport from a mixed‐type industrial area located ∼40 km northeast of Kinmen. Our study could partially fill the air quality data gap between the YRD and PRD regions, and highlight the alarming fact that air pollution has gradually expanded along eastern China’s coastal zone.